A modified polylactic acid-glycolic acid copolymer stent and preparation method thereof

By using a combination of gradient pore structure and composite hydrogel in bone tissue engineering scaffolding, composite hydrogel filled with ZIF-8 surface modified polyester microspheres, the problems of insufficient mechanical strength and insufficient antibacterial effect of existing scaffolds in bone tissue engineering are solved, and a scaffold with high mechanical strength, good cell compatibility and long-term antibacterial effect are achieved.

CN119770726APending Publication Date: 2025-04-08INST OF BIOLOGICAL & MEDICAL ENG GUANGDONG ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411944113.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing polylactic acid-glycolic acid copolymer scaffolds have problems in bone tissue engineering, such as degradation of acid production, lack of cell binding sites, insufficient mechanical strength, and difficulty in promoting bone regeneration and antibacterial effects at the same time.

Method used

Using a combination of gradient pore structure and composite hydrogel, the mechanical strength and cell adhesion of the scaffold are improved by filling the composite hydrogel with ZIF-8 surface modified polyester microspheres in the scaffold, and the degradation and antibacterial properties of the scaffold are promoted through the gradient pore structure.

Benefits of technology

The high mechanical strength of the scaffold, good cell compatibility and long-term antibacterial effect are achieved, and are suitable for the repair and regeneration of bone tissue defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005213239620000011
    Figure HDA0005213239620000011
  • Figure HDA0005213239620000012
    Figure HDA0005213239620000012
Patent Text Reader

Abstract

The present invention relates to the technical field of bone tissue engineering scaffolds, and discloses a modified polylactic-glycolic acid copolymer scaffold and a preparation method thereof. The modified polylactic-glycolic acid copolymer scaffold comprises a polylactic-glycolic acid copolymer scaffold with a gradient pore structure, and a composite hydrogel filled in the gradient pore structure; the composite hydrogel comprises a hydrogel solution and ZIF-8 surface-modified polyester microspheres dispersed therein. The modified polylactic-glycolic acid copolymer scaffold provided by the present invention has a gradient pore structure. Compared with the non-porous polylactic-glycolic acid copolymer scaffold, the specific surface area is increased, which is conducive to promoting the degradation of the scaffold, producing acidic degradation products, accelerating the degradation of ZIF-8 in the composite hydrogel, so that the scaffold exerts an antibacterial effect; the gradient pore structure can increase the surface roughness of the scaffold and enhance the cell adhesion of the scaffold. The scaffold has low in vitro cytotoxicity, no risk of hemolysis, and has osteogenic activity and long-lasting antibacterial effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bone tissue engineering scaffolds, and in particular to a modified polylactic acid-glycolic acid copolymer scaffold and a preparation method thereof. Background Art

[0002] 3D printing, also known as additive manufacturing technology, has unique advantages such as high precision, personalized manufacturing and complex shape construction, and has penetrated into all walks of life. At present, the more mature 3D printing technologies include photopolymerization 3D printing, fused deposition 3D printing, inkjet 3D printing and laser sintering 3D printing. Among them, the basic principle of fused deposition 3D printing technology is that the base material is heated in the nozzle to a temperature slightly higher than its melting point. Under the action of pressure, the base material is extruded from the nozzle into filaments. The nozzle moves in three dimensions under computer control, thereby stacking the base material filaments into shape.

[0003] The ideal bone tissue engineering scaffold should also have an interconnected porous network structure to provide interconnected channels for cell migration, ion transport, and cell-to-cell interaction. In addition, in order to cope with different parts, different injury conditions and different individual differences, personalized customization is also required. Conventional bone tissue engineering scaffold preparation methods such as foaming, sacrificial template method, freeze-drying method and casting method can no longer meet the needs. 3D printing technology can freely design the porosity and shape of the scaffold, which can well meet the needs of bone tissue engineering.

[0004] Polylactic acid-co-glycolic acid is a synthetic copolymer of polylactic acid and polyglycolic acid. It can be dissolved in a variety of solvents and has good biocompatibility. It can be used as a raw material to make 3D printed polylactic acid-co-glycolic acid scaffolds by melt deposition method at a melting temperature of 197°C. However, studies have found that polylactic acid-co-glycolic acid has defects such as degradation and acid production and lack of cell binding sites. At present, polylactic acid-co-glycolic acid is modified by introducing artificial materials through drug loading, surface modification, physical doping and chemical grafting to prepare new materials such as microsphere-filled polylactic acid-co-glycolic acid scaffolds. However, there are still problems such as insufficient osteogenic activity of the material, insufficient mechanical strength, difficulty in achieving the synergistic antibacterial effect of promoting bone regeneration at the same time, and complex preparation process and difficulty in industrialization, which greatly limits the application of 3D printed polylactic acid-co-glycolic acid scaffolds in bone tissue engineering. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a modified polylactic acid-co-glycolic acid scaffold; the second purpose of the present invention is to provide a preparation method of the modified polylactic acid-co-glycolic acid scaffold.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides a modified polylactic acid-glycolic acid copolymer scaffold, comprising a polylactic acid-glycolic acid copolymer scaffold with a gradient pore structure, and a composite hydrogel filled in the gradient pore structure; the composite hydrogel comprises a hydrogel solution and ZIF-8 surface-modified polyester microspheres dispersed therein.

[0008] In some embodiments of the present invention, the solid-liquid ratio of the gradient pore structure poly(lactic acid-glycolic acid) copolymer scaffold to the composite hydrogel is (4-10) mg:1 mL.

[0009] In some embodiments of the present invention, the size of the gradient pore structure is 1-100 μm.

[0010] In some embodiments of the present invention, the composite hydrogel comprises the following preparation raw materials: hydrogel, degradable polyester solution, zinc salt aqueous solution, organic ligand aqueous solution, surfactant aqueous solution and photoinitiator buffer.

[0011] In some embodiments of the present invention, the hydrogel is selected from at least one of methacrylated hyaluronic acid, methacrylated silk fibroin, methacrylated chondroitin sulfate, methacrylated chitosan, methacrylated carboxymethyl chitosan, methacrylated gelatin, methacrylated sodium alginate, hyaluronic acid, silk fibroin, chondroitin sulfate, chitosan, carboxymethyl chitosan, gelatin, and sodium alginate.

[0012] In the present invention, when the hydrogel is a methacrylated hydrogel, the problem that the scaffold is not conducive to cell survival in an acidic microenvironment can be avoided by utilizing its neutral solubility. When the hydrogel is sodium alginate or methacrylated sodium alginate, the bioactive ceramics in the scaffold and the divalent metal ions (such as Ca2+) released by the degradation of the ZIF-8 surface-modified polyester microspheres can be effectively prevented from oxidizing and degrading. 2+ 、Zn 2+ The hydrogel can cross-link sodium alginate or methacrylated sodium alginate to maintain the mechanical strength of the hydrogel. The hydrogel enables the scaffold to have personalized customization capabilities and good mechanical strength. The hydrogel with good hydrophilicity can be filled in the pores, and the hydrophilicity and hydrophobicity of the material can be further adjusted while maintaining the mechanical strength of the material, making it more suitable for the regeneration and repair of bone defects.

[0013] In some embodiments of the present invention, the degradable polyester solution is prepared by dissolving the degradable polyester in an organic solvent.

[0014] In some embodiments of the present invention, the molecular weight of the degradable polyester is 10,000-100,000 Da.

[0015] In some specific embodiments of the present invention, the degradable polyester is selected from at least one of polylactic acid, polylactic acid-glycolic acid copolymer, polycaprolactone, poly 3-hydroxyalkanoate, poly (3-hydroxybutyrate), poly 3-hydroxybutyrate-co-3-hydroxyvalerate, polytrimethylene carbonate, and polybutylene succinate.

[0016] In some embodiments of the present invention, the organic solvent is selected from at least one of dichloromethane, chloroform, tetrahydrofuran, ethyl acetate, dioxane, 1-methyl-2-pyrrolidone and dimethyl sulfoxide.

[0017] In some embodiments of the present invention, the zinc salt aqueous solution is prepared by dissolving a zinc salt in water.

[0018] In some embodiments of the present invention, the zinc salt is selected from at least one of zinc nitrate, zinc sulfate, zinc chloride and zinc acetate.

[0019] In some embodiments of the present invention, the organic ligand aqueous solution is prepared by dissolving an organic ligand in water.

[0020] In some embodiments of the present invention, the organic ligand is selected from at least one of 2-methylimidazole, benzimidazole and imidazole.

[0021] In some embodiments of the present invention, the surfactant aqueous solution is prepared by dissolving a surfactant in water.

[0022] In some embodiments of the present invention, the surfactant is selected from at least one of polyvinyl alcohol, gelatin, carboxymethyl cellulose, and methyl cellulose.

[0023] In some embodiments of the present invention, the photoinitiator buffer is prepared by mixing a photoinitiator with a buffer.

[0024] In some embodiments of the present invention, the photoinitiator includes lithium phenyl (2,4,6-trimethylbenzoyl) phosphate.

[0025] In some embodiments of the invention, the buffer comprises phosphate buffered saline (PBS buffer).

[0026] In some embodiments of the present invention, the composite hydrogel is prepared by a method comprising the following steps:

[0027] mixing a degradable polyester solution with an aqueous surfactant solution to obtain polyester microspheres;

[0028] The polyester microspheres are mixed with an organic ligand aqueous solution, and a zinc salt aqueous solution is added dropwise to obtain ZIF-8 surface-modified polyester microspheres;

[0029] The hydrogel is mixed with a photoinitiator buffer to obtain a hydrogel solution, which is then mixed with the ZIF-8 surface-modified polyester microspheres to obtain the composite hydrogel.

[0030] In some embodiments of the present invention, in the preparation of the composite hydrogel, the reaction conditions of the method are selected from one or more of the following:

[0031] A) the concentration of the degradable polyester solution is 30-80 mg / mL;

[0032] B) the concentration of the zinc salt aqueous solution is 5-25 mg / mL;

[0033] C) the concentration of the organic ligand aqueous solution is 20-90 mg / mL;

[0034] D) the ratio of the polyester microspheres, the organic ligand aqueous solution and the zinc salt aqueous solution is 1 g: (20-90) mL: (3-10) mL;

[0035] E) the photoinitiator buffer contains 0.1-0.5 wt % of the photoinitiator;

[0036] F) the solid-to-liquid ratio of the hydrogel to the photoinitiator buffer is (10-30) mg:1 mL;

[0037] G) The solid-to-liquid ratio of the hydrogel solution to the ZIF-8 surface-modified polyester microspheres is (40-100) mg:1 mL.

[0038] In some specific embodiments of the present invention, in the preparation of the composite hydrogel, the reaction conditions of the method are selected from one or more of the following:

[0039] A) the concentration of the degradable polyester solution is 40-70 mg / mL;

[0040] B) the concentration of the zinc salt aqueous solution is 8-25 mg / mL;

[0041] C) the concentration of the organic ligand aqueous solution is 25-85 mg / mL;

[0042] D) the ratio of the polyester microspheres, the organic ligand aqueous solution and the zinc salt aqueous solution is 1 g: (20-85) mL: (3-8) mL;

[0043] E) the photoinitiator buffer contains 0.2-0.4 wt % of the photoinitiator;

[0044] F) the solid-to-liquid ratio of the hydrogel to the photoinitiator buffer is (10-30) mg:1 mL;

[0045] G) The solid-to-liquid ratio of the hydrogel solution to the ZIF-8 surface-modified polyester microspheres is (40-100) mg:1 mL.

[0046] In some embodiments of the present invention, the process of preparing polyester microspheres is assisted by stirring; the stirring speed is 200-1000 rpm and the time is 10-25 hours.

[0047] In some embodiments of the present invention, the modified polylactic acid-co-glycolic acid scaffold comprises the following preparation raw materials: polylactic acid-co-glycolic acid, gluconolactone, a solvent and a composite hydrogel.

[0048] In some embodiments of the present invention, the molecular weight of the poly(lactic acid-co-glycolic acid) is 10,000-100,000 Da.

[0049] In some embodiments of the present invention, the solvent comprises a C1-C2 chloroalkane.

[0050] In some specific embodiments of the present invention, the solvent comprises dichloromethane.

[0051] In some embodiments of the present invention, the ratio of the poly(lactic acid-co-glycolic acid) copolymer, the solvent and gluconolactone is 1 g:(5-25) mL:(1-5) g.

[0052] In some specific embodiments of the present invention, the ratio of the polylactic acid-co-glycolic acid, the solvent and gluconolactone is 1 g:(5-20) mL:(1-4) g.

[0053] The second aspect of the present invention provides a method for preparing the modified poly(lactic acid-co-glycolic acid) scaffold according to the first aspect of the present invention, comprising the following steps:

[0054] S1, mixing polylactic acid-co-glycolic acid, a solvent and gluconolactone to obtain a gluconolactone / polylactic acid-co-glycolic acid solution, and drying to obtain a gluconolactone / polylactic acid-co-glycolic acid film;

[0055] S2, placing the gluconolactone / polylactic acid-co-glycolic acid film into a 3D printing barrel, printing layer by layer to obtain a polylactic acid-co-glycolic acid scaffold, and performing water bath sonication to obtain a polylactic acid-co-glycolic acid scaffold with a gradient pore structure;

[0056] S3, immersing the gradient pore structure polylactic acid-glycolic acid copolymer scaffold in the composite hydrogel, and solidifying it to obtain the modified polylactic acid-glycolic acid copolymer scaffold.

[0057] In some embodiments of the present invention, the printing parameters include at least one of the following parameters:

[0058] 1) The needle diameter is 0.1-0.6mm;

[0059] 2) The barrel temperature is 80-120°C;

[0060] 3) The needle temperature is 85-125°C;

[0061] 4) The fiber spacing is (0.7-0.9) mm × (0.7-0.9) mm;

[0062] 5) Printing speed is 5-20mm / s;

[0063] 6) The fiber orientation is 0°-90°;

[0064] 7) Air pressure is 300-500kPa;

[0065] 8) The layer height of the bioactive ceramic / polycaprolactone scaffold is 75%-95% of the needle diameter.

[0066] In some specific embodiments of the present invention, the printing parameters include at least one of the following parameters:

[0067] 1) The needle diameter is 0.1-0.5mm;

[0068] 2) The barrel temperature is 85-115°C;

[0069] 3) The needle temperature is 90-120°C;

[0070] 4) The fiber spacing is (0.7-0.9) mm × (0.7-0.9) mm;

[0071] 5) Printing speed is 6-18mm / s;

[0072] 6) The fiber orientation is 0°-90°;

[0073] 7) Air pressure is 350-450 kPa;

[0074] 8) The layer height of the bioactive ceramic / polycaprolactone scaffold is 75%-95% of the needle diameter.

[0075] In some embodiments of the present invention, the water bath ultrasound has a power of 600-2000 W and a time of 0.1-1 h.

[0076] In some embodiments of the present invention, the soaking time is 2-10 minutes.

[0077] In some embodiments of the present invention, the curing condition is 400-410nm blue light irradiation for 30-120s.

[0078] In some embodiments of the present invention, the process of preparing the gluconolactone / polylactic acid-co-glycolic acid solution is assisted by stirring; the stirring speed is 300-1000 rpm and the time is 45-100 hours.

[0079] In some embodiments of the present invention, the drying method is drying under natural ventilation conditions for 24-90 hours.

[0080] Compared with the prior art, the present invention has the following beneficial effects:

[0081] 1) The modified polylactic acid-co-glycolic acid scaffold provided by the present invention has a gradient pore structure. Compared with the non-porous polylactic acid-co-glycolic acid scaffold, the specific surface area is increased, which is conducive to promoting the degradation of the scaffold, generating acidic degradation products, and accelerating the degradation of ZIF-8 in the composite hydrogel so that the scaffold can play an antibacterial role; at the same time, the gradient pore structure can significantly improve the surface roughness of the scaffold and enhance the cell adhesion of the scaffold;

[0082] 2) The compressive strength of the modified polylactic acid-co-glycolic acid scaffold provided by the present invention is 7-9 MPa, which meets the mechanical strength requirements of human cancellous bone. By filling the pores with a composite hydrogel containing ZIF-8 surface-modified polyester microspheres, compared with filling a single hydrogel, not only the adverse effect of the pore structure on the compressive strength of the scaffold is reduced, but also the scaffold is endowed with antibacterial properties, thereby greatly improving the biological activity of the scaffold;

[0083] 3) The modified polylactic acid-co-glycolic acid scaffold provided by the present invention has low in vitro cytotoxicity, high biosafety, no risk of hemolysis, can well induce cells to secrete alkaline phosphatase, has osteogenic activity, and can also exert long-term antibacterial effects, and is suitable for the repair and regeneration of bone tissue defects under infection;

[0084] 4) The preparation method of the modified polylactic acid-glycolic acid copolymer scaffold provided by the present invention has simple process, low requirements on equipment, easy to obtain raw materials, low cost, and easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0085] Figure 1 is the compressive strength of the brackets in Examples 1-4 and Comparative Examples 1-5;

[0086] Figure 2 is the alkaline phosphatase activity of the scaffolds in Examples 1-4 and Comparative Examples 1-5. DETAILED DESCRIPTION

[0087] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0088] Example 1

[0089] In this embodiment, a modified poly(lactic acid-co-glycolic acid) copolymer stent is prepared in the following steps:

[0090] S11, dissolving 10 g of polylactic acid-co-glycolic acid (molecular weight 30000 Da) in 80 mL of dichloromethane, adding 10 g of gluconolactone, and magnetically stirring at 500 rpm for 72 h to obtain a gluconolactone / polylactic acid-co-glycolic acid solution; pouring the gluconolactone / polylactic acid-co-glycolic acid solution on a glass culture dish in a fume hood, and placing it in a ventilated state for 48 h to obtain a gluconolactone / polylactic acid-co-glycolic acid film;

[0091] S21, put the gluconolactone / polylactic acid-glycolic acid copolymer film into the 3D printing barrel, match it with a 0.25mm diameter needle, set the barrel temperature to 95°C, the needle temperature to 100°C, the fiber spacing to 0.8mm×0.8mm, the printing speed to 10mm / s, the fiber orientation to 0°-90°, the air pressure to 400kPa, the scaffold layer height to 80% of the needle diameter, and start printing layer by layer at a normal temperature platform to obtain a polylactic acid-glycolic acid copolymer scaffold; soak 60mg of the polylactic acid-glycolic acid copolymer scaffold in 10mL of water, and ultrasonicate at room temperature with a power of 1200W for 0.4h to obtain a gradient pore structure polylactic acid-glycolic acid copolymer scaffold;

[0092] S311, dissolving 1 g of polylactic acid (molecular weight 10000 Da) in 20 mL of dichloromethane to obtain a degradable polyester solution, adding the degradable polyester solution to 500 mL of an aqueous solution containing 10 g of 1799 type polyvinyl alcohol, stirring at 400 rpm at room temperature for 20 h, washing with water, centrifuging, and drying to obtain polyester microspheres;

[0093] S312, adding 0.75 g of polyester microspheres to 16 mL of a 48 mg / mL 2-methylimidazole aqueous solution, adding dropwise 3 mL of a 15 mg / mL zinc nitrate aqueous solution while stirring, washing, and drying to obtain ZIF-8 surface-modified polyester microspheres;

[0094] S313, dissolving 200 mg of methacryloyl sodium alginate in 10 mL of PBS solution containing 0.3 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution, and then adding 500 mg of ZIF-8 surface-modified polyester microspheres to obtain a composite hydrogel;

[0095] S314. Soak 50 mg of the gradient pore structure polylactic acid-glycolic acid copolymer scaffold in 10 mL of the composite hydrogel, take it out after dispersion for 4 minutes, irradiate it with 400 nm blue light for 60 seconds to solidify, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polylactic acid-glycolic acid copolymer scaffold.

[0096] Example 2

[0097] In this embodiment, a modified poly(lactic acid-co-glycolic acid) copolymer stent is prepared in the following steps:

[0098] S11, dissolving 10 g of polylactic acid-co-glycolic acid (molecular weight 100000 Da) in 200 mL of dichloromethane, adding 20 g of gluconolactone, and magnetically stirring at 400 rpm for 84 h to obtain a gluconolactone / polylactic acid-co-glycolic acid solution; pouring the gluconolactone / polylactic acid-co-glycolic acid solution on a glass culture dish in a fume hood, and placing it in a ventilated state for 72 h to obtain a gluconolactone / polylactic acid-co-glycolic acid film;

[0099] S21, put the gluconolactone / polylactic acid-glycolic acid copolymer film into the 3D printing barrel, match it with a 0.3mm diameter needle, set the barrel temperature to 115°C, the needle temperature to 120°C, the fiber spacing to 0.8mm×0.8mm, the printing speed to 12mm / s, the fiber orientation to 0°-90°, the air pressure to 450kPa, the scaffold layer height to 95% of the needle diameter, and start printing layer by layer at a normal temperature platform to obtain a polylactic acid-glycolic acid copolymer scaffold; soak 50mg of the polylactic acid-glycolic acid copolymer scaffold in 10mL of water, and ultrasonicate at 600W power for 0.8h at room temperature to obtain a gradient pore structure polylactic acid-glycolic acid copolymer scaffold;

[0100] S311, dissolving 1 g of polylactic acid-glycolic acid copolymer (molecular weight 30000 Da) in 24 mL of dimethyl sulfoxide to obtain a degradable polyester solution, adding the degradable polyester solution to 500 mL of an aqueous solution containing 2.5 g of carboxymethyl cellulose, stirring at 600 rpm at room temperature for 16 h, washing with water, centrifuging, and drying to obtain polyester microspheres;

[0101] S312, adding 0.4 g of polyester microspheres to 16 mL of a 60 mg / mL 2-methylimidazole aqueous solution, adding dropwise 2 mL of a 24 mg / mL zinc nitrate aqueous solution while stirring, washing, and drying to obtain ZIF-8 surface-modified polyester microspheres;

[0102] S313, dissolving 100 mg of methacryloyl carboxymethyl chitosan in 10 mL of PBS solution containing 0.4 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution, and then adding 240 mg of ZIF-8 surface-modified polyester microspheres to obtain a composite hydrogel;

[0103] S314. Soak 60 mg of the gradient pore structure polylactic acid-glycolic acid copolymer scaffold in 10 mL of the composite hydrogel, take it out after dispersion for 6 minutes, irradiate it with 400 nm blue light for 90 seconds to solidify, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polylactic acid-glycolic acid copolymer scaffold.

[0104] Example 3

[0105] In this embodiment, a modified poly(lactic acid-co-glycolic acid) copolymer stent is prepared in the following steps:

[0106] S11, dissolving 10g of polylactic acid-co-glycolic acid (molecular weight 10000Da) in 50mL of dichloromethane, adding 4g of gluconolactone, and magnetically stirring at 800rpm for 48h to obtain a gluconolactone / polylactic acid-co-glycolic acid solution; pouring the gluconolactone / polylactic acid-co-glycolic acid solution on a glass culture dish in a fume hood, and placing it in a ventilated state for 24h to obtain a gluconolactone / polylactic acid-co-glycolic acid film;

[0107] S21, put the gluconolactone / polylactic acid-glycolic acid copolymer film into the 3D printing barrel, match it with a 0.15mm diameter needle, set the barrel temperature to 85°C, the needle temperature to 90°C, the fiber spacing to 0.8mm×0.8mm, the printing speed to 6mm / s, the fiber orientation to 0°-90°, the air pressure to 350kPa, the scaffold layer height to 75% of the needle diameter, and start printing layer by layer at a normal temperature platform to obtain a polylactic acid-glycolic acid copolymer scaffold; soak 100mg of the polylactic acid-glycolic acid copolymer scaffold in 10mL of water, and ultrasonicate at 2000W power for 0.2h at room temperature to obtain a gradient pore structure polylactic acid-glycolic acid copolymer scaffold;

[0108] S311, dissolving 1 g of poly 3-hydroxyalkanoate (molecular weight 50000 Da) in 16 mL of chloroform to obtain a degradable polyester solution, adding the degradable polyester solution to 500 mL of an aqueous solution containing 50 g of 124 type polyvinyl alcohol, stirring at 250 rpm at room temperature for 24 h, washing with water, centrifuging, and drying to obtain polyester microspheres;

[0109] S312, adding 1 g of polyester microspheres to 16 mL of 84 mg / mL 2-methylimidazole aqueous solution, adding dropwise 3 mL of 16 mg / mL zinc nitrate aqueous solution while stirring, washing, and drying to obtain ZIF-8 surface-modified polyester microspheres;

[0110] S313, dissolving 150 mg of methacrylylated silk fibroin in 10 mL of PBS solution containing 0.25 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution, and then adding 960 mg of ZIF-8 surface-modified polyester microspheres to obtain a composite hydrogel;

[0111] S314. Soak 40 mg of the gradient pore structure polylactic acid-glycolic acid copolymer scaffold in 10 mL of the composite hydrogel, disperse it for 2 minutes, take it out, irradiate it with 400 nm blue light for 30 seconds to solidify it, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polylactic acid-glycolic acid copolymer scaffold.

[0112] Example 4

[0113] In this embodiment, a modified poly(lactic acid-co-glycolic acid) copolymer stent is prepared in the following steps:

[0114] S11, dissolving 10g of polylactic acid-co-glycolic acid (molecular weight 60000Da) in 120mL of dichloromethane, adding 15g of gluconolactone, and magnetically stirring at 300rpm for 96h to obtain a gluconolactone / polylactic acid-co-glycolic acid solution; pouring the gluconolactone / polylactic acid-co-glycolic acid solution on a glass culture dish in a fume hood, and placing it in a ventilated state for 60h to obtain a gluconolactone / polylactic acid-co-glycolic acid film;

[0115] S21, put the gluconolactone / polylactic acid-glycolic acid copolymer film into the 3D printing barrel, match it with a 0.45mm diameter needle, set the barrel temperature to 105°C, the needle temperature to 110°C, the fiber spacing to 0.8mm×0.8mm, the printing speed to 18mm / s, the fiber orientation to 0°-90°, the air pressure to 420kPa, the scaffold layer height to 90% of the needle diameter, and start printing layer by layer at a normal temperature platform to obtain a polylactic acid-glycolic acid copolymer scaffold; soak 80mg of the polylactic acid-glycolic acid copolymer scaffold in 10mL of water, and ultrasonicate at 1000W power for 0.6h at room temperature to obtain a gradient pore structure polylactic acid-glycolic acid copolymer scaffold;

[0116] S311, dissolving 1 g of 3-hydroxybutyrate-co-3-hydroxyvalerate (molecular weight 100000 Da) in 18 mL of chloroform to obtain a degradable polyester solution, adding the degradable polyester solution to 500 mL of an aqueous solution containing 5 g of gelatin, stirring at 1000 rpm at room temperature for 12 h, washing with water, centrifuging, and drying to obtain polyester microspheres;

[0117] S312, adding 0.5 g of polyester microspheres to 16 mL of a 28 mg / mL 2-methylimidazole aqueous solution, adding dropwise 4 mL of an 8 mg / mL zinc nitrate aqueous solution while stirring, washing, and drying to obtain ZIF-8 surface-modified polyester microspheres;

[0118] S313, dissolving 300 mg of methacrylylated silk fibroin in 10 mL of a PBS solution containing 0.5 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution, and then adding 400 mg of ZIF-8 surface-modified polyester microspheres to obtain a composite hydrogel;

[0119] S314. Soak 80 mg of the gradient pore structure polylactic acid-glycolic acid copolymer scaffold in 10 mL of the composite hydrogel, take it out after dispersion for 10 minutes, irradiate it with 400 nm blue light for 120 seconds to solidify it, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polylactic acid-glycolic acid copolymer scaffold.

[0120] Comparative Example 1

[0121] This comparative example prepares a modified polylactic acid-glycolic acid copolymer scaffold, which differs from Example 1 in that no gluconolactone is added and no gradient pore structure is formed by ultrasound. The preparation steps are as follows:

[0122] S21, put 10g of polylactic acid-co-glycolic acid (molecular weight 30000Da) into the 3D printing barrel, match it with a 0.25mm diameter needle, set the barrel temperature to 95°C, the needle temperature to 100°C, the fiber spacing to 0.8mm×0.8mm, the printing speed to 10mm / s, the fiber orientation to 0°-90°, the air pressure to 400kPa, the scaffold layer height to 80% of the needle diameter, and start printing layer by layer at room temperature to obtain a polylactic acid-co-glycolic acid scaffold;

[0123] S311, dissolving 1 g of polylactic acid (molecular weight 10000 Da) in 20 mL of dichloromethane to obtain a degradable polyester solution, adding the degradable polyester solution to 500 mL of an aqueous solution containing 10 g of 1799 type polyvinyl alcohol, stirring at 400 rpm at room temperature for 20 h, washing with water, centrifuging, and drying to obtain polyester microspheres;

[0124] S312, adding 0.75 g of polyester microspheres to 16 mL of a 48 mg / mL 2-methylimidazole aqueous solution, adding dropwise 3 mL of a 15 mg / mL zinc nitrate aqueous solution while stirring, washing, and drying to obtain ZIF-8 surface-modified polyester microspheres;

[0125] S313, dissolving 200 mg of methacryloyl sodium alginate in 10 mL of PBS solution containing 0.3 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution, and then adding 500 mg of ZIF-8 surface-modified polyester microspheres to obtain a composite hydrogel;

[0126] S314. Soak 50 mg of the polylactic acid-glycolic acid copolymer scaffold in 10 mL of the composite hydrogel, disperse it for 4 minutes, take it out, irradiate it with 400 nm blue light for 60 seconds to solidify it, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polylactic acid-glycolic acid copolymer scaffold.

[0127] Comparative Example 2

[0128] This comparative example prepares a modified polylactic acid-glycolic acid copolymer scaffold, which is different from Example 1 in that only a single hydrogel is added. The preparation steps are as follows:

[0129] S11, dissolving 10 g of polylactic acid-co-glycolic acid (molecular weight 30000 Da) in 80 mL of dichloromethane, adding 10 g of gluconolactone, and magnetically stirring at 500 rpm for 72 h to obtain a gluconolactone / polylactic acid-co-glycolic acid solution; pouring the gluconolactone / polylactic acid-co-glycolic acid solution on a glass culture dish in a fume hood, and placing it in a ventilated state for 48 h to obtain a gluconolactone / polylactic acid-co-glycolic acid film;

[0130] S21, put the gluconolactone / polylactic acid-glycolic acid copolymer film into the 3D printing barrel, match it with a 0.25mm diameter needle, set the barrel temperature to 95°C, the needle temperature to 100°C, the fiber spacing to 0.8mm×0.8mm, the printing speed to 10mm / s, the fiber orientation to 0°-90°, the air pressure to 400kPa, the scaffold layer height to 80% of the needle diameter, and start printing layer by layer at a normal temperature platform to obtain a polylactic acid-glycolic acid copolymer scaffold; soak 60mg of the polylactic acid-glycolic acid copolymer scaffold in 10mL of water, and ultrasonicate at room temperature with a power of 1200W for 0.4h to obtain a gradient pore structure polylactic acid-glycolic acid copolymer scaffold;

[0131] S313, dissolving 200 mg of methacryloyl sodium alginate in 10 mL of a PBS solution containing 0.3 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution;

[0132] S314. Soak 50 mg of the gradient pore structure polylactic acid-glycolic acid copolymer scaffold in 10 mL of the hydrogel solution, disperse it for 4 minutes, take it out, irradiate it with 400 nm blue light for 60 seconds to solidify it, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polylactic acid-glycolic acid copolymer scaffold.

[0133] Comparative Example 3

[0134] This comparative example prepares a modified polylactic acid-glycolic acid copolymer scaffold, which differs from Example 1 in that no composite hydrogel is added. The preparation steps are as follows:

[0135] S11, dissolving 10 g of polylactic acid-co-glycolic acid (molecular weight 30000 Da) in 80 mL of dichloromethane, adding 10 g of gluconolactone, and magnetically stirring at 500 rpm for 72 h to obtain a gluconolactone / polylactic acid-co-glycolic acid solution; pouring the gluconolactone / polylactic acid-co-glycolic acid solution on a glass culture dish in a fume hood, and placing it in a ventilated state for 48 h to obtain a gluconolactone / polylactic acid-co-glycolic acid film;

[0136] S21. Place the gluconolactone / polylactic acid-glycolic acid copolymer film into a 3D printing barrel, match it with a 0.25 mm diameter needle, set the barrel temperature to 95°C, the needle temperature to 100°C, the fiber spacing to 0.8 mm×0.8 mm, the printing speed to 10 mm / s, the fiber orientation to 0°-90°, the air pressure to 400 kPa, the scaffold layer height to 80% of the needle diameter, and start printing layer by layer at room temperature to obtain a polylactic acid-glycolic acid copolymer scaffold; soak 60 mg of the polylactic acid-glycolic acid copolymer scaffold in 10 mL of water, and ultrasonicate at 1200 W power for 0.4 h at room temperature to obtain a gradient pore structure polylactic acid-glycolic acid copolymer scaffold, which is a modified polylactic acid-glycolic acid copolymer scaffold.

[0137] Comparative Example 4

[0138] This comparative example prepares a modified polylactic acid-co-glycolic acid scaffold, which differs from Example 1 in that no gluconolactone is added, no gradient pore structure is formed by ultrasound, and only a single hydrogel is added. The preparation steps are as follows:

[0139] S21, put 10g of polylactic acid-co-glycolic acid (molecular weight 30000Da) into the 3D printing barrel, match it with a 0.25mm diameter needle, set the barrel temperature to 95°C, the needle temperature to 100°C, the fiber spacing to 0.8mm×0.8mm, the printing speed to 10mm / s, the fiber orientation to 0°-90°, the air pressure to 400kPa, the scaffold layer height to 80% of the needle diameter, and start printing layer by layer at room temperature to obtain a polylactic acid-co-glycolic acid scaffold;

[0140] S313, dissolving 200 mg of methacryloyl sodium alginate in 10 mL of a PBS solution containing 0.3 wt % of phenyl-2,4,6-trimethylbenzoyl lithium phosphite to obtain a hydrogel solution;

[0141] S314. Soak 50 mg of the polylactic acid-glycolic acid copolymer scaffold in 10 mL of the hydrogel solution, disperse it for 4 minutes, take it out, irradiate it with 400 nm blue light for 60 seconds to solidify it, freeze the product in a -20°C refrigerator, and then freeze-dry it to obtain a modified polylactic acid-glycolic acid copolymer scaffold.

[0142] Comparative Example 5

[0143] In this comparative example, a polylactic acid-co-glycolic acid copolymer stent is prepared, and the preparation steps are as follows:

[0144] S21. Put 10g of polylactic acid-glycolic acid copolymer (molecular weight 30000Da) into the 3D printing barrel, match it with a 0.25mm diameter needle, set the barrel temperature to 95°C, the needle temperature to 100°C, the fiber spacing to 0.8mm×0.8mm, the printing speed to 10mm / s, the fiber orientation to 0°-90°, the air pressure to 400kPa, the bracket layer height to 80% of the needle diameter, and start printing layer by layer at room temperature to obtain a polylactic acid-glycolic acid copolymer bracket.

[0145] Performance Testing

[0146] 1. The stents prepared in Examples 1-4 and Comparative Examples 1-5 were subjected to mechanical strength tests:

[0147] After the stent is dried, it is placed in an INSTON test machine (34sc -5 ) with a compression speed of 1 mm / min, and the mechanical properties of the scaffold were analyzed.

[0148] Figure 1 is the compressive strength of the brackets in Examples 1-4 and Comparative Examples 1-5, Figure 1 It can be seen that the compressive strength of the modified polylactic acid-co-glycolic acid scaffold prepared in Examples 1-4 is 7-9MPa, which meets the mechanical strength requirements of human cancellous bone; compared with the scaffold in Example 1, the scaffold in Comparative Example 1 does not contain a porous structure, and its compressive strength is relatively high; the scaffolds in Comparative Examples 2 and 3 do not contain ZIF-8 surface-modified polyester microspheres, and their compressive strength is significantly reduced; the scaffolds in Comparative Examples 4 and 5 also do not contain ZIF-8 surface-modified polyester microspheres, but because they do not contain a porous structure at the same time, their compressive strength is between the scaffold in Example 1 and the scaffolds in Comparative Examples 2 and 3. It shows that in the process of manufacturing a gradient pore structure for composite hydrogel filling, the porous structure will reduce the mechanical properties of the material, but the ZIF-8 surface-modified polyester microspheres in the composite hydrogel will reduce the adverse effects of the porous structure on the compressive strength, so that the compressive strength of the modified polylactic acid-co-glycolic acid scaffold meets the use requirements.

[0149] 2. In vitro cytotoxicity evaluation of the scaffolds prepared in Examples 1-4 and Comparative Examples 1-5:

[0150] The test was carried out in accordance with GB / T 16886.5-2017 “Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Test”.

[0151] L929 mouse fibroblasts that had been cultured for 24 hours and were growing vigorously were digested and prepared to a density of 1.0×10 5 / mL, inoculated in a 96-well plate, 100μL per well. After the cells grow into a monolayer, remove the original culture medium, add 100μL of the test sample extract, blank control solution, positive control solution and negative control solution, respectively, with 6 replicates in each group. After the addition of samples, place the 96-well plate in a 37℃, 5% CO2 incubator for 24h. After 24h, aspirate the original culture medium, add 50μL 1mg / mL MTT to each well, and continue to culture for 2h. After the end, aspirate the supernatant, add 100μL 99.5% pure isopropanol to dissolve the crystals; measure the absorbance value on the microplate reader with 570nm as the main absorption wavelength and 650nm as the reference wavelength to calculate the cell survival rate.

[0152] The cell viability was calculated according to the following formula: Cell viability (%) = 100 × OD 570e / OD570 b

[0153] Where, OD 570e OD is the average optical density of the test sample or control sample extract; 570b is the average optical density of the blank.

[0154] Table 1 In vitro cytotoxicity evaluation results of the scaffolds in Examples 1-4 and Comparative Examples 1-5

[0155] Group Survival rate (%) Group Survival rate (%) Blank control group 100 Example 4 86.95 Negative control group 88.16 Comparative Example 1 86.83 Positive control group 17.61 Comparative Example 2 85.67 Example 1 87.16 Comparative Example 3 86.07 Example 2 86.54 Comparative Example 4 83.45 Example 3 87.03 Comparative Example 5 81.46

[0156] Table 1 shows the in vitro cytotoxicity evaluation results of the scaffolds in Examples 1-4 and Comparative Examples 1-5. It can be seen from Table 1 that the modified polylactic acid-glycolic acid copolymer scaffold provided by the present invention has low in vitro cytotoxicity, the cell survival rate generally reaches more than 86%, and the biosafety is relatively high.

[0157] 3. Hemolytic performance test of the stents prepared in Examples 1-4 and Comparative Examples 1-5:

[0158] According to the amount of blood used in the experiment, collect blood from healthy rabbit hearts. If 10 mL of blood is collected, add 0.5 mL of potassium oxalate solution with a mass concentration of 20 g / L to prepare fresh anticoagulated rabbit blood. Take 8 mL of fresh anticoagulated rabbit blood and dilute it with 10 mL of sodium chloride injection with a mass concentration of 9 g / L. Add the test sample to the test group according to the extraction ratio, and then add 10 mL of sodium chloride injection. Add 10 mL of sodium chloride to each tube of the negative control group and 10 mL of distilled water to each tube of the positive control group. Each group operates 3 tubes in parallel. After all test tubes are placed in a constant temperature water bath at (37±1)℃ for 30 minutes, add 0.2 mL of diluted rabbit blood to each test tube, mix gently, and continue to keep warm in a (37±1)℃ water bath for 60 minutes. Pour out the liquid in the tube and centrifuge at 800g for 5 minutes. Aspirate the supernatant and transfer it to a cuvette, and measure the absorbance at a wavelength of 545nm using a spectrophotometer. The absorbance of the test group and the control group is the average value of three tubes. The absorbance of the negative control tube should not be greater than 0.03, and the absorbance of the positive control tube should be 0.8±0.3, otherwise the test should be repeated.

[0159] The formula for calculating the hemolysis rate is: Hemolysis rate (%) = (absorbance of the test sample group - absorbance of the negative control group) / (absorbance of the positive control group - absorbance of the negative control group) * 100%

[0160] Table 2 Hemolytic performance test results of the stents in Examples 1-4 and Comparative Examples 1-5

[0161] Group Hemolysis rate (%) Group Hemolysis rate (%) Example 1 2.16 Comparative Example 1 2.72 Example 2 3.05 Comparative Example 2 3.02 Example 3 3.15 Comparative Example 3 2.51 Example 4 2.46 Comparative Example 4 2.75 Comparative Example 5 3.06

[0162] Table 2 shows the hemolysis performance test results of the stents in Examples 1-4 and Comparative Examples 1-5. It can be seen from Table 2 that the hemolysis rates of the modified polylactic acid-glycolic acid copolymer stents provided by the present invention are all less than 4%, and there is no hemolysis risk.

[0163] 4. In vitro osteogenic differentiation test of pre-osteoblasts induced by the scaffolds prepared in Examples 1-4 and Comparative Examples 1-5:

[0164] After irradiation sterilization, the scaffolds prepared in Examples 1-4 and Comparative Examples 1-5 were immersed in DMEM basal culture medium at a concentration of 10 mg / mL and placed in a 37°C shaker at 120 rpm for 24 hours. After the extraction, the mixture of the scaffold and the culture medium was centrifuged at 1000 rpm and the supernatant was collected. The collected extracts were diluted 2 times with the corresponding DMEM culture medium, and finally 10% fetal bovine serum was added to obtain a conditioned medium.

[0165] MC3T3-E1 cells were plated at 1×10 5The cells were inoculated in a 24-well plate at a density of 100 μg / mL. After 24 hours of adherent culture, the conditioned medium was replaced and cultured in an incubator at 37°C and 5% CO2. The culture medium was replaced every 2-3 days. After 7 days of culture, the osteogenic differentiation performance was detected by alkaline phosphatase secreted by MC3T3-E1 cells. The pNPP method was used for determination. The specific steps were as follows: After the cells were washed with PBS solution, they were immersed in a PBS solution containing 0.1 mol / L glycine, 1 mmol / L magnesium chloride and 0.05% Triton X-100 (octoxynol). After the cells were dissolved, the dissolved solution was evenly mixed with disodium p-nitrophenyl phosphate, and the mixed solution was placed at 37°C for 30 minutes. Subsequently, the mixed solution was added dropwise to a 96-well plate, and the absorbance of each well at a wavelength of 405 nm was measured using an ELISA reader.

[0166] Definition of alkaline phosphatase activity unit: In diethanolamine (DEA) buffer at pH = 9.8, at 37°C, the amount of alkaline phosphatase required to hydrolyze p-nitrophenyl phosphate chromogenic substrate to produce 1 μmol p-nitrophenol per minute is defined as one enzyme activity unit, also known as one DEA enzyme activity unit. In glycine buffer at pH = 9.6, at 25°C, the amount of alkaline phosphatase required to hydrolyze p-nitrophenyl phosphate chromogenic substrate to produce 1 μmol p-nitrophenol per minute is defined as one enzyme activity unit, also known as one Glycine enzyme activity unit. One Glycine enzyme activity unit is approximately equivalent to 3 DEA enzyme activity units. According to the definition of enzyme activity, calculate the alkaline phosphatase activity in the sample.

[0167] Figure 2 is the alkaline phosphatase activity of the scaffolds in Examples 1-4 and Comparative Examples 1-5, Figure 2 It can be seen that the modified polylactic acid-co-glycolic acid scaffolds prepared in Examples 1-4 all have a good effect of inducing cells to secrete alkaline phosphatase. Compared with the scaffold in Example 1, the scaffold in Comparative Example 1 does not contain a porous structure, and its osteogenic activity is slightly reduced; the scaffolds in Comparative Examples 2 and 3 do not contain ZIF-8 surface-modified polyester microspheres, and their alkaline phosphatase activity is significantly reduced; the scaffolds in Comparative Examples 4 and 5 do not contain ZIF-8 surface-modified polyester microspheres, nor do they have a porous structure, and their alkaline phosphatase activity is the lowest. The test results show that when the polylactic acid-co-glycolic acid scaffold has a porous structure and the pores are filled with composite hydrogels, the alkaline phosphatase activity of the scaffold is the highest.

[0168] 5. Antibacterial performance test of the stents prepared in Examples 1-4 and Comparative Examples 1-5:

[0169] Take fresh slant cultures of Staphylococcus aureus and Escherichia coli, count the live bacteria in the bacterial suspension, and prepare a diluent (0.03 mol / L PBS (pH = 7.2-7.4) containing 1% peptone) to a bacterial count of 5 × 10 5 -10×10 6 cfu / mL bacterial suspension. Place the scaffold samples in sterile plates, add 50μL of bacterial suspension to each sample, record the time of adding bacteria to each tube, inoculate the blood plate 60min after adding bacteria, and place the sample in a 5mL nutrient broth tube. Incubate the blood plate and broth tube inoculated with bacteria at 37℃ for 48h, observe the preliminary results, and continue to culture in the sterile growth tube until the 28th day. If the broth tube is turbid and the blood plate has bacterial growth, it is recorded as positive, indicated by (+); if it is still clear on the 35th day, it is considered as sterile growth, indicated by (–).

[0170] Table 3 Antibacterial performance test results of the stents in Examples 1-4 and Comparative Examples 1-5

[0171] Group Staphylococcus aureus Escherichia coli Example 1 - - Example 2 - - Example 3 - - Example 4 - - Comparative Example 1 + + Comparative Example 2 + + Comparative Example 3 + + Comparative Example 4 + + Comparative Example 5 + +

[0172] Table 3 shows the antibacterial performance test results of the stents in Examples 1-4 and Comparative Examples 1-5. It can be seen from Table 3 that the modified polylactic acid-co-glycolic acid stents prepared in Examples 1-4 all have good antibacterial effects and can grow aseptically for 35 days. However, in Comparative Examples 2-5, since the stents do not contain ZIF-8 surface-modified polyester microspheres, it is impossible to use the rapid release of Zn in the acidic microenvironment of bacterial infection. 2+ The antibacterial effect of the modified polylactic acid-co-glycolic acid scaffold provided by the present invention is long-lasting and can be used for the repair and regeneration of bone tissue defects under infection.

Claims

1. A modified polylactic acid-co-glycolic acid stent, characterized in that: The invention comprises a polylactic acid-glycolic acid copolymer scaffold with a gradient pore structure and a composite hydrogel filled in the gradient pore structure; the composite hydrogel comprises a hydrogel solution and ZIF-8 surface-modified polyester microspheres dispersed therein.

2. The modified polylactic acid-co-glycolic acid stent according to claim 1, characterized in that: The solid-liquid ratio of the gradient pore structure polylactic acid-glycolic acid copolymer scaffold and the composite hydrogel is (4-10) mg:1 mL.

3. The modified poly(lactic acid-co-glycolic acid) stent according to claim 1, characterized in that: The size of the gradient pore structure is 1-100 μm.

4. The modified poly(lactic acid-co-glycolic acid) stent according to claim 1, characterized in that: The composite hydrogel comprises the following preparation raw materials: hydrogel, degradable polyester solution, zinc salt aqueous solution, organic ligand aqueous solution, surfactant aqueous solution and photoinitiator buffer; And / or, the composite hydrogel is prepared by a method comprising the following steps: mixing a degradable polyester solution with an aqueous surfactant solution to obtain polyester microspheres; The polyester microspheres are mixed with an organic ligand aqueous solution, and a zinc salt aqueous solution is added dropwise to obtain ZIF-8 surface-modified polyester microspheres; the hydrogel is mixed with a photoinitiator buffer to obtain a hydrogel solution, which is then mixed with the ZIF-8 surface-modified polyester microspheres to obtain the composite hydrogel.

5. The modified poly(lactic acid-co-glycolic acid) stent according to claim 4, characterized in that: In the preparation of the composite hydrogel, the reaction conditions of the method are selected from one or more of the following: A) the concentration of the degradable polyester solution is 30-80 mg / mL; B) the concentration of the zinc salt aqueous solution is 5-25 mg / mL; C) the concentration of the organic ligand aqueous solution is 20-90 mg / mL; D) the ratio of the polyester microspheres, the organic ligand aqueous solution and the zinc salt aqueous solution is 1 g: (20-90) mL: (3-10) mL; E) the photoinitiator buffer contains 0.1-0.5 wt % of the photoinitiator; F) the solid-to-liquid ratio of the hydrogel to the photoinitiator buffer is (10-30) mg:1 mL; G) The solid-to-liquid ratio of the hydrogel solution to the ZIF-8 surface-modified polyester microspheres is (40-100) mg:1 mL.

6. The modified poly(lactic acid-co-glycolic acid) stent according to any one of claims 1 to 5, characterized in that: The modified polylactic acid-glycolic acid copolymer scaffold comprises the following preparation raw materials: polylactic acid-glycolic acid copolymer, gluconolactone, solvent and composite hydrogel.

7. The modified poly(lactic acid-co-glycolic acid) stent according to claim 6, characterized in that: The ratio of the polylactic acid-glycolic acid copolymer, the solvent and gluconolactone is 1 g: (5-25) mL: (1-5) g.

8. The method for preparing the modified polylactic acid-co-glycolic acid stent according to claim 6 or 7, characterized in that: The following steps are involved: S1, mixing polylactic acid-co-glycolic acid, a solvent and gluconolactone to obtain a gluconolactone / polylactic acid-co-glycolic acid solution, and drying to obtain a gluconolactone / polylactic acid-co-glycolic acid film; S2, placing the gluconolactone / polylactic acid-co-glycolic acid film into a 3D printing barrel, printing layer by layer to obtain a polylactic acid-co-glycolic acid scaffold, and performing water bath sonication to obtain a polylactic acid-co-glycolic acid scaffold with a gradient pore structure; S3, immersing the gradient pore structure polylactic acid-glycolic acid copolymer scaffold in the composite hydrogel, and solidifying it to obtain the modified polylactic acid-glycolic acid copolymer scaffold.

9. The preparation method according to claim 8, characterized in that: The printing parameters include at least one of the following parameters: 1) The needle diameter is 0.1-0.6mm; 2) The barrel temperature is 80-120°C; 3) The needle temperature is 85-125°C; 4) The fiber spacing is (0.7-0.9) mm × (0.7-0.9) mm; 5) Printing speed is 5-20mm / s; 6) The fiber orientation is 0°-90°; 7) Air pressure is 300-500kPa; 8) The layer height of the bioactive ceramic / polycaprolactone scaffold is 75%-95% of the needle diameter.

10. The preparation method according to claim 8, characterized in that: The power of the water bath ultrasound is 600-2000W; the time is 0.1-1h; And / or, the soaking time is 2-10 min; And / or, the curing condition is 400-410nm blue light irradiation for 30-120s.